Fresh, hardened and durability properties of concrete made with flyash and limestone based Portland composite cement - Mohapatra, B. N.; Kaura, Puneet; Ojha, P N; Singh, Brijesh; Kumar, Sumit; Liju, Varsha (Journal of Asian Concrete Federation, 2023)
Clinker substitution with alternative cementitious materials is one of the way to develop low clinker cement. In this work, three compositions of Portland composite cement (PCC) were prepared by inter-grinding of clinker, gypsum, flyash and limestone where limestone content were kept as 5 %, 7 % and 10 % and flyash content kept as 25% & 35 %. In the present work, study was conducted at 0.60 w/c and in total 4 concrete mixes were designed including one control mix (made with PPC). Fresh properties like air content & fresh density, hardened properties like compressive strength, flexural strength & drying shrinkage and durability behaviour of concrete made with PCC was compared with control concrete. Various durability tests like Rapid chloride permeability test (RCPT), electrical resistivity, accelerated carbonation and sulphate resistance test were carried out to evaluate the performance of concrete made with PCC. The study indicates that with limited addition of limestone i.e., up to 10%, early strength as well as later age strength increases marginally. This may be due to the synergistic effect of flyash and limestone. However, durability aspect was influenced by limestone addition. Test results of RCPT, electrical resistivity as well as sulphate attack indicates the dilution effect of limestone dominates over other physical effects that leads to an overall increase in effective w/c ratio whereas carbonation depth is predominantly affected by the fly as content.